2019
DOI: 10.3390/ma12040673
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Noise Investigation of 1.09 μm GaAsBi Laser Diodes

Abstract: GaAsBi is a suitable and very attractive material system to be used as an active layer in laser diodes (LDs). To understand the performance and the reliability of such devices and also for further laser diode improvements, the origin of noise sources should be clarified. A detailed study of near-infrared 1.09 μm wavelength GaAsBi type-I laser diodes using the low-frequency noise spectroscopy in a temperature range of (180–300) K is presented. Different types of voltage fluctuation spectral density dependencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…[ 63 ] The lasing wavelength was 1135 nm at 273 K under CW operation and 1142 nm at up to 350 K in pulsed mode. In 2019, the low‐frequency of noise characteristics of GaAsBi ([Bi] = 8%) were investigated by Glemža et al [ 64 ] To date, the longest optically pumped lasing wavelength is 1407 nm, reported by Liu et al in 2019, with a 5.8% Bi content. [ 57 ] This laser used a microdisk structure, which has great potential for application in modern photonic integration compared with the Fabry–Perot‐based design.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 63 ] The lasing wavelength was 1135 nm at 273 K under CW operation and 1142 nm at up to 350 K in pulsed mode. In 2019, the low‐frequency of noise characteristics of GaAsBi ([Bi] = 8%) were investigated by Glemža et al [ 64 ] To date, the longest optically pumped lasing wavelength is 1407 nm, reported by Liu et al in 2019, with a 5.8% Bi content. [ 57 ] This laser used a microdisk structure, which has great potential for application in modern photonic integration compared with the Fabry–Perot‐based design.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 99%
“…However, hydrogen passivation did not remove the deep‐level defect located at 0.33 eV above the VBM induced by Bi Ga , consistent with observation reported by Pettinari et al [ 133 ] Besides, facet passivation may reduce low‐frequency noise of GaAsBi laser diodes due to surface leakage. [ 64 ] Sulfur passivation treatment on the facet surface has been shown to reduce surface states in GaAs laser diodes, increase the threshold for the onset of catastrophic optical degradation (COD) in InGaAs and AlGaInP laser diodes and improve the reliability of InGaAsP laser diodes. [ 135–138 ] To date, the effect of sulfur passivation on the facet surface of GaAsBi laser diodes has not been reported.…”
Section: Postgrowth Processingmentioning
confidence: 99%
“…[60] The lasing wavelength was 1135 nm at 273 K under CW operation and 1142 nm at up to 350 K in pulsed mode. In 2019, the low-frequency of noise characteristics of GaAsBi ([Bi] = 8 %) were investigated by Glemža et al [64] To date, the longest optically pumped lasing wavelength is 1407 nm, reported by Liu et al in 2019, with a 5.8 % Bi content. [57] This laser used a microdisk structure, which has great potential for application in modern photonic integration compared to the Fabry-Perotbased design.…”
Section: Figurementioning
confidence: 99%
“…Besides, facet passivation may reduce low frequency noise of GaAsBi laser diodes due to surface leakage. [64] Sulfur passivation treatment on the facet surface has been shown to reduce surface states in GaAs laser diodes, increase the threshold for the onset of catastrophic optical degradation (COD) in InGaAs and AlGaInP laser diodes and improve the reliability of InGaAsP laser diodes. [137][138][139][140] To date, the effect of sulfur passivation on the facet surface of GaAsBi laser diodes has not been reported.…”
Section: Passivationmentioning
confidence: 99%
“…Although their technology is well developed, applications of the GaAs- and (Al, Ga)As-based LDs are held back by losses caused by the Auger non-radiative recombination and temperature-sensitivity of the radiation wavelength. In our previous works, the advantages of the introduction of Bi into the GaAs lattice by substituting As for optoelectronic devices were demonstrated [ 7 , 8 ]. It is well known that Bi presence modifies the GaAs bandgap leading to the partial suppression of the non-radiative Auger recombination: with incorporation of Bi atoms into the GaAs lattice, the valence band is mainly modified, while the change in the conducting band is significantly weaker.…”
Section: Introductionmentioning
confidence: 99%